FUNCTIONAL MULTILINGUALISM IN DIGITAL LINGUISTIC LANDSCAPES: NEGOTIATING ISLAMIC IDENTITY AND GLOBAL ENGAGEMENT - Faridah, Faridah; Fitria, Hilyati; Nasution, Sahkholid; Fithriani, Rahmah (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2026)
The digital linguistic landscape of university websites has become an important site for examining how multilingual practices reflect institutional identity and globalization. However, limited attention has been given to how multilingual language choices simultaneously negotiate Islamic identity and global engagement within digital environments. This study aims to examine how Indonesian, Arabic, and English are strategically employed in university websites to construct institutional identity and support internationalization. A qualitative research design was adopted using Critical Discourse Analysis (CDA). The data comprised 29 official State Islamic University websites selected through purposive sampling based on institutional status and multilingual accessibility. Secondary data were collected from publicly accessible website pages and analyzed through descriptive categorization, percentage analysis, thematic interpretation, and CDA to identify multilingual patterns and their underlying ideological meanings. The findings reveal that only a limited number of websites consistently implement Indonesian, Arabic, and English. English predominantly functions as the language of internationalization and global communication, whereas Arabic is primarily employed as a symbolic marker of Islamic identity and is implemented inconsistently across website content. The study introduces the concept of functional multilingualism, demonstrating that different languages perform complementary institutional roles rather than equal communicative functions in digital environments. These findings suggest that university websites serve as ideological spaces where institutional identity and globalization are continuously negotiated. The study contributes to digital linguistic landscape scholarship by extending linguistic landscape research beyond language distribution toward ideological interpretation and offers practical implications for developing coherent multilingual language policies that balance international visibility with institutional identity.